Pemberdayaan Perempuan Dalam Meningkatkan Kesejahteraan Ekonomi Keluarga - bertha beloan; Rostini; Nisma Iriani; Nurmillah Ilyas; Andi Jamaluddin; Harniati; Syahribulan (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
AbstractThe role of women today can no longer be underestimated, because it is undeniable that the current public world has accepted a "new occupant" named women. Not infrequently he even acts as a man as a breadwinner and a supporter of family finances. Women come into the public world and do jobs that have been dominated by men. Women are no longer known as housewives who only wrestle in the kitchen, well, and bed. Realizing the importance of women today, it is appropriate for women to get something to improve their quality. Empowerment of women is expected to be one way to improve its quality so that the position of women is no longer only as a connoisseur of rupiah for the “adam” but also as a producer of rupiah for the family. The research method used is descriptive qualitative which is expected to help in exploring the potential of women to improve their quality. This research was conducted during community service in Kassi Village and the research subjects were women in Kassi Village as many as 50 people. Data was collected through interviews and FGD in women's empowerment workshops. The results showed that most of the women in Kassi Village had a high interest in earning a living to support the household economy. Therefore, it is necessary to conduct training and empower women in Kassi village.